Focus groups in the metaverse: shared virtual spaces for patients, clinicians, and researchers - Amestoy Alonso, Benat; Donegan, Tony; Calvis, Isaac; Swidrak, Justyna; Rodriguez, Edgar; Vargas-Reverón, Caribay L.; Combalia, Andrés; Oliva Martinez, Ramon; Sanchez-Vives, Maria V. (Frontiers in Virtual Reality, 2024)
Patient focus groups can be invaluable for facilitating user-centered design of medical devices and new technologies, effectively capturing the richness and depth of patient experiences to help thoroughly assess feasibility, tolerance, and usability. While the metaverse holds promise for healthcare applications, its use in patient focus groups remains unexplored. In this Perspective we discuss the potential of the metaverse for conducting focus groups with patients. The theme of the focus group was the design and development of a therapeutic virtual reality application for patients with chronic low back pain. We carried out a pilot study comparing a focus group in a shared virtual space versus a physical location. This experience was positively received by patients, researchers, and clinicians, suggesting the metaverse is a viable medium for conducting these meetings and has potential advantages for remotely located participants, opening the doors for future expansion beyond focus groups to encompass all kinds of patient support and information groups. This approach fosters patientcentered healthcare by helping to facilitate patient voices directly into the design process, which may help lead to improved healthcare delivery, patient satisfaction, and treatment outcomes.